International Culture Awareness: Indonesia-Thailand Joint Community Service - Kukuh Arisetyawan; Aminudin Ma‘ruf; Tony Seno Aji; Hendry Cahyono; Wenny Restikasari; Prattana Srisuk; Nico Irawan; Safa Kharisma (International Journal Of Community Service, 2024)
The introduction of Indonesian culture is carried out through an understanding of ethnicity, art, language, and customs. This cultural sharing is considered effective as a means to promote the nation's culture and increase understanding between nations as a bridge to improve cross-cultural understanding and strengthen bilateral relations between the two countries. By introducing Indonesia's cultural diversity to the Thai people, it is hoped that it can increase understanding of the importance of culture as a form of national identity and maintain social harmony. By using the observation approach, sharing season, and presentation to identify the impact of the introduction of Indonesian culture on the perception of Thai society, with the main focus on cultural understanding, we can establish international cooperation. This study shows that this cultural introduction initiative can enrich Indonesia's cultural insights in the Thailand community, especially in Thai Global Business Administration Technological College (TGBC), as well as make them aware of the importance of culture as a national asset that must be preserved and appreciated. This can open up opportunities for cooperation in academic and non-academic fields, which will later create a closer and mutually beneficial relationship between the two countries.